The transformation and reshaping of South African languages via cell-phone messaging: sms speak as a local practice - Davids, Gaironesa (University of the Western Cape, 2015)
Magister Artium - MA === South Africa is a diverse, multilingual country with a majority of its youth owning or using cellular phone technologies. The cell phone interaction between multilingual individuals from different linguistic and cultural backgrounds suggests that a range of multilingual styles are being developed in the electronic domain, particularly when sending SMSes (Short Message Service messages). This study uses the Systemic Functional Linguistics Perspective (SFL) to analyse how English, Afrikaans and isiXhosa are being transformed through the medium of text messaging at the University of the Western Cape (UWC). In using methods such as thematic analysis and SFL this research is interested in the linguistic choices individuals make when engaging in SMS/Mxit messages to express themselves. The study aims to look at the effects of concepts such as globalization, stylization, polylingual languaging and transidiomatic practices on text messaging itself; and in turn to see how these text messages are typified by the mixing and blending of languages and their multimodal aspects are then considered to be a coherent and cohesive social practice among the youth. In addition, considering new developments in language studies, particularly the notions of language as social practice and hybrid languaging practices, it also looks at SMS/Mxit messages and examines them against the ‘traditional’ monolingual concepts of codeswitching and code-mixing. The linguistic analysis of this text based data presents a framework for exploring how members of the youth portray their identities as it allows the researcher to deal with interpersonal dimensions of language in texts in a systematic manner. These interpersonal dimensions view the relationships between participants in relation to their performance of identity. Drawing on SMS/Mxit data from 60 third year university students, the focus of this thesis is to investigate if the languages used during SMS/Mxit interactions are being modified and transformed by this medium of communication. It simultaneously looks at these student communicators performing a range of identity options. The study concludes that English, Afrikaans and isiXhosa are not used as separate language entities but are instead used as one language resource. It highlights how speakers use features of any language as linguistic options for a communicative event. Ultimately, the study demonstrates that SMS speak is not seen as an alternative language used within a third space but has instead become a norm in terms of language practices among the youth.